High levels of hemolysis do not affect measurement of PAPP-A, β-HCG and TRAb on BRAHMS KRYPTOR compact plus - Pettersson Pablo, Paul; Aneskans, Cecilia; Vink, Martin (Scandinavian journal of clinical and laboratory investigation, 2023)
To assess the impact of high levels of hemolysis on the laboratory results for free β-hCG, PAPP-A, and TRAb performed on the B·R·A·H·M·S KRYPTOR Compact PLUS. Adapted from the CLSI guidelines EP07-A2, paired difference testing was performed on serum samples from the routine laboratory workflow. Three sample pools for each assessed analyte was prepared and subjected to increased levels of added hemolysate. For β-hCG and PAPP-A, the relative difference in the measured analyte concentration between the sample with 0 g/L added Hb and the samples with increasing free Hb concentrations (up to 6 g/L), was well below the pre-set acceptance criterion of 10% at all levels. The TRAb results showed greater variation than the other analytes, likely a consequence of imprecision rather than hemolysis. Hemolysis has a negligible effect on the analysis results of free beta-hCG, PAPP-A and TRAb measured on the B·R·A·H·M·S KRYPTOR Compact PLUS.